All the colors of night - Krentz, Jayne Ann (Berkley, 2021)
"Two gifted people fall deep into the dark world of ancient secrets in this second installment of the new chilling Fogg Lake series by New York Times bestselling author Jayne Ann Krentz. North Chastain has always had the mysterious ability to channel energy through crystals. He and his father both have the ability, which is what the doctors believe is the cause of his father's sudden coma. But North knows that isn't the case. He's convinced it was brought on by an artifact his father had been looking for--and found. With his unique talent of channeling energy through crystals, North has the best chance at recovering the artifact, but he also needs someone who knows the shadowy world of crazy collectors, deceptive dealers, and dangerous raiders. Sierra Raines is looking for a fresh start after a failed gig at a major auction house. With her reputation ruined, she turns to the murky backwaters of the paranormal artifacts trade. She takes commissions to find, acquire, and transport objects that are hot commodities in the antiquities world, staying in the shadows to avoid attracting the attention of the Foundation. When North Chastain approaches her, Sierra takes him on as a client, though not without reservations. They wind up in Fogg Lake, and soon discover that they will have to trust each other in order to not only save North's father but also to survive"--
Keywords: Psychics -- Fiction; Crystals -- Fiction; Antiquities -- Fiction; Romantic suspense fiction; Thrillers (Fiction); Fantasy fiction; Romance fiction